How French general practitioners adapt their care to patients with social difficulties? - Annie De Oliveira; Barbara Chavannes; Magali Steinecker; Mady Denantes; Julie Chastang; Gladys Ibanez (Family Medicine and Community Health, 2019)
Objective Several studies have shown the role of the primary care system in access to care and in reducing social inequalities in health. The objective of this study was to describe the practices of general practitioners (GPs) in taking into account the social environment of their patient, and the ways they adapted to social difficulties.Design Qualitative study comprising interviews and focus groups.Setting French primary care settings.Participants Twenty semistructured interviews and two focus groups were conducted with 33 GPs. Sessions were audio recorded, transcribed verbatim and analysed using thematic analysis. The reporting of findings was guided by consolidated criteria for reporting qualitative research.Result This study identified adaptations at three levels: in the individual management of patients (alert system, full involvement in prevention, better communication, prioritised additional examinations, financial facilities, help in administrative tasks), in the collective management of patients in an office (consultation without appointment, pay-for-performance indicators, medical staffs, multidisciplinary protocols, medical practice in group, medical student), and in the community management (patients description, cooperation with associations, public health sector and politics).Conclusion In France, GPs can take into account the social determinants of health in practice through simple or more complex actions.